Global developmental delay in a child with asphyxia neonatorum: Why search for an additional explanation? - Surpure, Shreyas A; Rathod, Bhavesh (Indian Journal of Child Health, 2023)
Children presenting neurological problems and a history of “not cried immediately at birth” are labeled to have cerebral palsy due to birth asphyxia. Although this may be true in many situations, the presence of some additional features may help determine an alternate diagnosis. We present such a case with an alternate diagnosis. A child with a history of birth asphyxia was labeled as a case of global developmental delay or a case of cerebral palsy by the treating doctors. However, the child had certain dysmorphic features such as bulbous nose, depressed nasal bridge, low-set ears, high-arched palate, squint, and flat feet. The child was initially treated in the Neonatal Intensive Care Unit after birth. Later, she developed various neurological features, with frequent episodes of aspiration pneumonia and seizures which were managed with anticonvulsant drugs and antimicrobial agents. She also had some additional non-specific features. On detailed evaluation, the child was diagnosed to have 1q43q44 microdeletion. Search for an alternate or additional diagnosis should be carried out if a child presenting with global developmental delay has some additional syndromic features. This will help in the prognostication of child and help parents in future pregnancy.